Does fiscal transparency matter for bank development? A lookup on emerging and developing countries - Emna Trabelsi (Journal of Central Banking Theory and Practice, 2023)
This paper examines how fiscal transparency is linked to bank development. It also hypothesizes that the effect is mediated by reasonable channel(s). Drawing upon a panel dataset of emerging and developing economies, we find that fiscal transparency is positively related to the private credit and to the ratio of liquid assets, implying that more transparent policies enhance bank development. Our panel regressions and the mediation analysis also suggest that the effect of fiscal transparency on private credit is significantly transmitted through the control of corruption, while it has a direct effect on the ratio of liquid assets.
Keywords: C23; E52; E58; E62; 330; fiscal transparency; bank development; dynamic panel; mediation; bootstrapping